2023
DOI: 10.3390/ijms24065446
|View full text |Cite
|
Sign up to set email alerts
|

Eptifibatide, an Older Therapeutic Peptide with New Indications: From Clinical Pharmacology to Everyday Clinical Practice

Abstract: Therapeutic peptides are oligomers or short polymers of amino acids used for various medical purposes. Peptide-based treatments have evolved considerably due to new technologies, stimulating new research interests. They have been shown to be beneficial in a variety of therapeutic applications, notably in the treatment of cardiovascular disorders such as acute coronary syndrome (ACS). ACS is characterized by coronary artery wall damage and consequent formation of an intraluminal thrombus obstructing one or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 106 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…While initial studies have shown promising results more extensive investigations are required to conrm its therapeutic value. 258,259 Captopril (Fig. 11) is the rst angiotensin-converting enzyme (ACE) inhibitor, a drug class used to treat high blood pressure.…”
Section: Ripps On the Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…While initial studies have shown promising results more extensive investigations are required to conrm its therapeutic value. 258,259 Captopril (Fig. 11) is the rst angiotensin-converting enzyme (ACE) inhibitor, a drug class used to treat high blood pressure.…”
Section: Ripps On the Marketmentioning
confidence: 99%
“…While initial studies have shown promising results more extensive investigations are required to confirm its therapeutic value. 258,259…”
Section: Advanced Ripp (Candidate) Drugsmentioning
confidence: 99%
“…Eptifibatide is used most commonly under its brand name, Integrilin, and is one of several GP 2b/3a inhibitors acting as a therapeutic peptide [ 49 ]. Integrilin has played a critical role as part of a range of first-generation integrin antagonists, where it accompanies Abciximab, known as Reopro, and Tirofiban, known as Aggrastat [ 50 ].…”
Section: Reviewmentioning
confidence: 99%